Pengaruh Pendapatan Asli Daerah, Dana Perimbangan dan Belanja Modal terhadap Kinerja Keuangan Pemerintah Kabupaten/Kota di Pulau Sumatera Tahun 2021 - Resa Novita; Fefri Indra Arza (Universitas Negeri Padang, 2024)
This study aims to analyze the effect of local original income, balancing funds, and capital expenditure on the financial performance of district/city governments on the island of Sumatra in 2021. This study used a quantitative approach. The samples taken in this study were based on predetermined criteria. The results of the sample selection of 106 regional governments which are Regency / City regional governments on the island of Sumatra in 2021. Multiple regression analysis to test the hypothesis was carried out using SPPS 29 which showed the results of the study that local original revenue had a significant positive effect on local government financial performance, while balancing funds and capital expenditure had a significant negative effect on local government financial performance.